2009
DOI: 10.1103/physrevb.79.045317
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced long-lived spin excitations in two-dimensional spin-orbit coupled systems

Abstract: Rigorous coupled spin-charge drift-diffusion equations are derived from quantum-kinetic equations for the spin-density matrix that incorporate effects due to k-linear spin-orbit interaction, an electric field, and the elastic scattering on nonmagnetic impurities. The explicit analytical solution for the induced magnetization exhibits a pole structure, from which the dispersion relations of spin excitations are identified. Applications of the general approach refer to the excitation of long-lived field-induced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…For example, when both the Rashba and Dresselhaus spin-orbit couplings exist, by tuning the two to be comparable, the spin diffusion length can be greatly increased [18,29,32,34,[337][338][339][340]. Such enhancement of spin diffusion length has been achieved in a recent experiment, where the control over both the doping asymmetry and well width was shown to be effective to manipulate the relative strength of the Rashba and Dresselhaus spin-orbit couplings and hence the spin diffusion length [37].…”
Section: Spin Relaxation and Spin Dephasingmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, when both the Rashba and Dresselhaus spin-orbit couplings exist, by tuning the two to be comparable, the spin diffusion length can be greatly increased [18,29,32,34,[337][338][339][340]. Such enhancement of spin diffusion length has been achieved in a recent experiment, where the control over both the doping asymmetry and well width was shown to be effective to manipulate the relative strength of the Rashba and Dresselhaus spin-orbit couplings and hence the spin diffusion length [37].…”
Section: Spin Relaxation and Spin Dephasingmentioning
confidence: 92%
“…However, in semiconductors it has been shown that the inhomogeneous broadening usually dominates spin diffusion [25,28,336], which breaks down the above relation [32,35]. The inhomogeneous broadening in spin diffusion and transport is different from that in spin relaxation in the time domain: an electron in a different k state has a different velocity and/or spin precession frequency (k) (e.g., due to the spin-orbit coupling), making the spin propagation frequency along the spin diffusion direction (n) kdependent ∼ Ω(k)/(k·n) [25,28,29,336,337]. This inhomogeneous broadening can not be removed by traditional spin-echo.…”
Section: Spin Relaxation and Spin Dephasingmentioning
confidence: 95%
See 1 more Smart Citation
“…4 and 8. More generally, the relaxation of the spin helix is an example of situations [1][2][3][4][5][9][10][11][12][13][14][15][16][17][18] in which the electron spin relaxation scenario deviates from the predictions of D'yakonov-Perel' theory. 19 Experimentally, the spin-grating technique 20 is typically used 3,5 to create spin helical configurations in semiconductors.…”
mentioning
confidence: 99%
“…Second, other quantum kinetic approaches focus exclusively on the spinorbit coupling [61][62][63][64] . Third, the transport in high and low magnetic fields itself is involved due to precession motions of charged particles and treated approximately [65][66][67][68][69][70][71] . Fourth, the interaction with scalar and magnetic impurities requires a certain spin-coupling which is important for transport effects in ferromagnetic materials [72][73][74] .…”
Section: Introduction a Motivation And Outlinementioning
confidence: 99%